SWOT Analysis of Arabic Language Courses at the Modern Islamic Boarding School of Shohibul Muslimin - Millata Hanifa,; Royhan Imamul Muttaqin,; Wira Kusuma,; Alifa Nurfitri, (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
This study aims to analyze the Arabic language learning process through courses applied at the Shohibul Muslimin Modern Islamic Boarding School using a SWOT analysis approach. This Islamic Boarding School emphasizes the learning model of learning by practicing. This strategy aims to produce a generation of students who are theoretically superior and have applicative experience in the use of Arabic. This research uses qualitative methods with observation, interview, and documentation techniques. The results showed that the main strength lies in the supportive environment of the Islamic boarding school and the quality of competent teaching staff. However, there are weaknesses, such as the low interest of students due to the complexity of Arabic vocabulary and difficulty understanding the material, which requires intensive repetition. Threats to the implementation of the course include the internal social sanctions some students feel, such as shaving their hair for not attending the course. Nevertheless, there are significant opportunities in the form of a gradual increase in the student's communicative abilities in Arabic, especially in listening and speaking skills. This finding indicates that the hands-on approach positively impacts learning Arabic in an Islamic boarding school environment.